Novel Silicon Doped Tin Oxide–Carbon Microspheres as Anode Material for Lithium Ion Batteries: The Multiple Effects Exerted by Doped Si. Issue 48 (10th November 2017) - Tan, Yuanzhong; Wong, Ka‐Wai; Ng, Ka Ming
Abstract: Silicon doped tin oxide embedded porous carbon microspheres (Si y Sn1– y O x @C) are synthesized. It is found that the doped Si not only improves the reversibility of lithiation/delithiation reactions, but also prevents Sn from aggregation. In addition, the doped Si introduces extra defects into the carbon matrix and produces Li + conductive Li4 SiO4, which accelerates Li + diffusion. Together with the conductive, porous carbon matrix that provides void space to accommodate the volume change of Sn during charge/discharge cycling, the novel Si y Sn1– y O x @C exhibits excellent electrochemical performance. It shows a high initial columbic efficiency of 75.9%. A charge (delithiation) capacity of 880.32 mA h g −1 is retained after 150 cycles, i.e., 91% of the initial capacity. These results indicate that the as‐synthesized Si y Sn1– y O x @C is a promising anode material for lithium ion batteries. Abstract : Si doped tin oxide–porous carbon microspheres (Si y Sn1– y O x @C) with uniformly dispersed Sn and Si are successfully prepared by a new synthetic method using sodium gluconate as the carbon source. This novel composite exhibits high capacity, excellent cyclability, and outstanding rate capability, showing that it is a promising anode material for lithium ion batteries.